2002
DOI: 10.1074/jbc.m108062200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glis2, a Novel Gene Encoding a Gli-related, Krüppel-like Transcription Factor with Transactivation and Repressor Functions

Abstract: In this study, we describe the characterization of a gene encoding a novel Krü ppel-like protein, named Glis2. Glis2 encodes a relatively proline-rich, basic 55.8-kDa protein. Its five tandem Cys 2 -His 2 zinc finger motifs exhibit the highest homology to those of members of the Gli and Zic subfamilies of Krü ppel-like proteins. Confocal microscopic analysis demonstrated that Glis2 localizes to the nucleus. Analysis of the genomic structure of the Glis2 gene showed that it is composed of 6 exons separated by 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 80 publications
3
94
0
Order By: Relevance
“…They derive from two cell populations, ectodermal epithelial buds and surrounding mesenchymal mesoderm, and unexpected parallels exist between MpTs development and vertebrate nephrogenesis (Denholm et al, 2003). Several fly MpT genes such as Kr, cut, hibris and Odd have vertebrate homologues (Glis2, Cux1, nephrin and Osr, respectively) implicated in kidney development (Sharma et al, 2004;Tena et al, 2007;Vanden Heuvel et al, 1996;Zhang et al, 2002). We have previously shown that stellate cells within MpT express two related zinc-finger transcription factors, teashirt (tsh) and tiptop (tio) (Denholm et al, 2003;Laugier et al, 2005).…”
Section: Teashirt 3 Is Necessary For Ureteral Smooth Muscle Differentmentioning
confidence: 99%
“…They derive from two cell populations, ectodermal epithelial buds and surrounding mesenchymal mesoderm, and unexpected parallels exist between MpTs development and vertebrate nephrogenesis (Denholm et al, 2003). Several fly MpT genes such as Kr, cut, hibris and Odd have vertebrate homologues (Glis2, Cux1, nephrin and Osr, respectively) implicated in kidney development (Sharma et al, 2004;Tena et al, 2007;Vanden Heuvel et al, 1996;Zhang et al, 2002). We have previously shown that stellate cells within MpT express two related zinc-finger transcription factors, teashirt (tsh) and tiptop (tio) (Denholm et al, 2003;Laugier et al, 2005).…”
Section: Teashirt 3 Is Necessary For Ureteral Smooth Muscle Differentmentioning
confidence: 99%
“…Expressions of Gli2 and -3, however, were reported in craniofacial structures and mesenchyme surrounding the vibrissal follicle. The expression pattern of Glis1 differs considerably to that of the recently described family member Glis2, which is found predominantly in neural tissues and somites (50,75).…”
Section: Figmentioning
confidence: 69%
“…Comparison of the amino acid sequence of Glis1 with those in the GenBank TM data base revealed that its ZFD exhibited high homology with those of the Krü ppel-like zinc finger proteins of the Gli and Zic subfamily (7,9,18,48,49), the recently described Glis2 (50), and with the ZFD of the Drosophila Gli-like zinc finger protein glf/Lmd (40,41) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zic genes are characterized by the presence of a zinc-finger domain (ZFD) that typically contains two cysteines and two histidines (C2-H2) that fold in a tetrahedral configuration around a central zinc ion (Pavletich and Pabo, 1993). Each Zic transcription factor contains five tandem repeats of the C2-H2 ZFD, which is highly homologous to the ZFD sequences of the Gli and Glis transcription factor families (Aruga et al, 1994(Aruga et al, , 1996aKim et al, 2002;Zhang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%